Transcriptome profiling of aged-mice ovaries administered with individual ingredients of Samul-tang - Hyejin Shin; Jihyun Kim; Musun Park; Heeseon Jo; Myunggyo Lee; Seongwon Cha; Haeseung Lee; Sooseong You (Scientific Data)
Abstract Samul-tang (SM) is a traditional multi-ingredient herbal formula that is widely used in clinical practice for treating female infertility. Despite its known therapeutic benefits, the complexity of its action mechanisms owing to the combination of multiple compounds has limited its research and integration into modern pharmacological science. To address this challenge, we identified 38 herbal compounds as the major ingredients in SM and generated their transcriptome data from aged-mice ovaries by administering these individual compounds. This dataset provides a resource for investigating the action mechanisms of SM and assist in identifying effective combinations of ingredients that can reproduce the therapeutic effects of SM.